MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK MELALUI PERMAINAN SEPAK BOLA PADA KELOMPOK B DI TK ISLAM TERPADU INSAN UTAMA 2 JL. IKHLAS KOTA PEKANBARU - Alvan Hafiz Rahmarinaldi; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:Grossmotoricisbodymovementsusinglargemusclesandthephysicaldevelopmentofchildren.theprobleminthisresearchlackofoutdooractivityorphysicaleducationinPAUD,sothattheimpactonthemovementandpostureofchildren,PAUDmustmaximizeitsroletohelpincreasethediverseneedsofstudentsinthe process ofdeveloping gross motoric skills.This research aimsto determine efforts toimprovegross motor skillsingroup BIslamTerpaduInsan Utama2 kindergartenthroughasoccergames.Thisresearchisaquantitativeandqualitativeresearch.Datacollectionmethodistotalsampling.ThepopulationinthisresearchwasthechildrenofgroupBinTkIslamTerpaduInsan2inthe2018/2019academicyeartotaling 15people,consistingof9boysand6girls.TheinstrumentusedischecklistbyWinasanjaya(2009: 93). Gross motoricskills,saidtobeobserved from theresultsofobservation anddocumentationdataobtained from eachcycle.Onthe indicatorkickingthe ball, can be seen that the initial condition of the child before the action shows that inthe pre-action there are only 4 children at (26,67%), in cycle 1 developed into 7children(46.67%)andincycle2developedtoreach14children(93.33%).Onthebalanceindicatorbeforetheaction,namelyinthepre-actiontheareonly4children(26,67%), incycle1developedinto11children(73.33%), andincycle2developedinto15children(100%)fromtheaverageincreasein grossmotoricskill,thisresearchshowstheresultsnamely(78.33%)wherethisincreaseshowsthatthe grossmotorabilitiesofchildrenhavereachedgoodcriteria,becausetheyhaveachievedtheindicators of success that have been set. Key Words: Gross Motoric, Soccer